Effective online privacy mechanisms with persuasive communication - Coopamootoo, P L (Cranfield University, 2016)
This thesis contributes to research by taking a social psychological perspective to managing privacy online. The thesis proposes to support the effort to form a mental model that is required to evaluate a context with regards to privacy attitudes or to ease the effort by biasing activation of privacy attitudes. Privacy being a behavioural concept, the human-computer interaction design plays a major role in supporting and contributing to end users’ ability to manage their privacy online. However, unless privacy attitudes are activated or made accessible, end users’ behaviour would not necessarily match their attitudes. This perspective contributes to explaining why online privacy mechanisms have long been found to be in-effective. Privacy academics and practitioners are queried for their opinions on aspects of usable privacy designs. Evaluation of existing privacy mechanisms (social network service, internet browsers privacy tabs and E-Commerce websites) for privacy experts’ requirements reveals that the privacy mechanisms do not provide for the social psychological processes of privacy management. This is determined through communication breakdowns within the interaction design and the lack of privacy disclosure dialectical tension, lack of disclosure context and visibility of privacy means. The thesis taps into established research in social psychology related to the attitude behaviour relationship. It proposes persuasive communication to support the privacy management process that is to enable end user control of their privacy while ensuring typical usability criteria such as minimum effort and ease of use. An experimental user study within an E-Commerce context provides evidence that in the presence of persuasive triggers that support the disclosure and privacy dialectic within a context of disclosure; end users can engage in privacy behaviour that match their privacy concerns. Reminders for privacy actions with a message that is personally relevant or has a privacy argument result in significantly more privacy behaviour than a simple reminder. However, reminders with an attractive source that is not linked with privacy can distract end users from privacy behaviour such that the observed response is similar to the simple reminder. This finding is significant for the research space since it supports the use of persuasive communication within human-computer interaction of privacy designs as a powerful tool in enabling attitude activation and accessibility such that cognitive evaluation of an attitude object can be unleashed and end users can have a higher likelihood of responding with privacy behaviour. It also supports the view that privacy designs that do not consider their interaction with privacy attitudes or their influence on behaviour can turn out to be in-effective although found to support the typical usability criteria. More research into the social-psychological aspects of online privacy management would be beneficial to the research space. Further research could determine the strength of activated or accessed privacy attitude caused by particular persuasive triggers and the extent of privacy behaviour. Longitudinal studies could also be useful to better understand online privacy behaviour and help designs of more effective and usable online privacy.